Employee Performance at PT. Pos Indonesia Persero Medan Barat Medan City: The Impact of Psychological Workload and Internal Work Environment - Tania Ulfa Yavi AR; Abd. Rasyid Syamsuri (Garuda Prestasi Nusantara Consulting, 2022)
The purpose of this study is to determine the impact of psychological workload and the internal work environment on the performance of PT. Pos Indonesia Persero Medan Barat Medan City personnel. This study employs a quantitative approach. This study began in November 2021 and ended in April 2022. Observation, documentation studies, and questionnaires were employed to obtain data in this study. The employees of PT. Pos Indonesia Persero Medan Barat Medan City, a total of 62 people, will be studied. A quota sampling technique was used to sample all populations. The multiple linear regression method was employed with the SPSS application as the analytical method. The study's findings show that psychological workload affects employee performance in a good and significant way. Employee performance is influenced by the internal work environment in a favorable and important way. Employee performance is influenced by the overall psychological workload and the internal work environment. The coefficient of determination (R2) in this study is 0.640, indicating that the psychological workload and the internal work environment account for 64% of employee performance.